Escherichia coli alcohol dehydrogenase YahK is a protein that binds both iron and zinc - Liang,Feng; Sun,Shujuan; Zhou,YongGuang; Peng,Tiantian; Xu,Xianxian; Li,Beibei; Tan,Guoqiang (PeerJ, 2024)
Background Previous studies have highlighted the catalytic activity of Escherichia coli alcohol dehydrogenase YahK in the presence of coenzyme nicotinamide adenine dinucleotide (NAD) and metal zinc. Notably, competitive interaction between iron and zinc ligands has been shown to influence the catalytic efficiency of several key proteases. This study aims to unravel the intricate mechanisms underlying YahK’s catalytic action, with a particular focus on the pivotal roles played by metal ions zinc and iron. Methods The purified YahK protein from E. coli cells cultivated in LB medium was utilized to investigate its metal-binding properties through UV-visible absorption measurements and determination of metal content. Subsequently, the effects of excess zinc and iron on the metal-binding ability and alcohol dehydrogenase activity of the YahK protein were explored using M9 minimal medium. Furthermore, site-directed mutagenesis technology was employed to determine the iron-binding site location within the YahK protein. Polyacrylamide gel electrophoresis was conducted to examine the relationship between iron and zinc with respect to the YahK protein. Results The study confirmed the presence of iron and zinc in the YahK protein, with the zinc-bound form exhibiting enhanced catalytic activity in alcohol dehydrogenation reactions. Conversely, the presence of iron appears to play a pivotal role in maintaining overall stability of the YahK protein. Furthermore, experimental findings indicate that excessive zinc within M9 minimal medium can competitively bind to iron-binding sites on YahK, thereby augmenting its alcohol dehydrogenase activity. Conclusion The dynamic binding of YahK to iron and zinc unveils its intricate regulatory mechanism as an alcohol dehydrogenase, thereby highlighting the possible physiological role of YahK in E. coli and its significance in governing cellular metabolic processes. This discovery provides a novel perspective for further investigating the specific impact of metal ion binding on YahK and E. coli cell metabolism.
Keywords: YahK; Iron ions; Zinc ions; Alcohol dehydrogenase; NADP+